Identification of key genes and pathways involved in vitiligo development based on integrated analysis. Issue 31 (31st July 2020) - Lei, Zixian; Yu, Shirong; Ding, Yuan; Liang, Junqin; Halifu, Yilinuer; Xiang, Fang; Zhang, Dezhi; Wang, Hongjuan; Hu, Wen; Li, Tingting; Wang, Yunying; Zou, Xuelian; et al.
Abstract : Abstract: Vitiligo is a chronic skin condition lack of melanocytes. However, researches on the aetiology and pathogenesis of vitiligo are still under debate. This study aimed to explore the key genes and pathways associated with occurrence and development of vitiligo. Weighted gene coexpression network analysis (WGCNA) was applied to reanalyze the gene expression dataset GSE65127 systematically. Functional enrichments of these modules were carried out at gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), gene set variation analysis (GSVA), and gene set enrichment analysis (GSEA). Then, a map of regulatory network was delineated according to pivot analysis and drug prediction. In addition, hub genes and crucial pathways were validated by an independent dataset GSE75819. The expressions of hub genes in modules were also tested by quantitative real-time polymerase chain reaction (qRT-PCR). Eight coexpressed modules were identified by WGCNA based on 5794 differentially expressed genes of vitiligo. Three modules were found to be significantly correlated with Lesional, Peri-Lesional, and Non-Lesional, respectively. The persistent maladjusted genes included 269 upregulated genes and 82 downregulated genes. The enrichments showed module genes were implicated in immune response, p53 signaling pathway, etc. According to GSEA and GSVA, dysregulated pathways were activated incessantly from Non-Lesional to Peri-Lesional and then to Lesional, 4 of which were verified by an independent dataset GSE75819. Finally, 42 transcription factors and 228 drugs were spotted. Focusing on the persistent maladjusted genes, a map of regulatory network was delineated. Hub genes ( CACTIN, DCTN1, GPR143, HADH, MRPL47, NKTR, NUF2 ) and transcription factors ( ITGAV, SYK, PDPK1 ) were validated by an independent dataset GSE75819. In addition, hub genes ( CACTIN, DCTN1, GPR143, MRPL47, NKTR) were also confirmed by qRT-PCR. The present study, at least, might provide an integrated and in-depth insight for exploring the underlying mechanism of vitiligo and predicting potential diagnostic biomarkers and therapeutic targets. Abstract : Supplemental Digital Content is available in the text